Istikshāf al-Takfīr wa Uṣūluhu wa Istikhdāmātuhu: Muqāranat Kufr al-Ta’wīl bayna al-Ashā‘irah wa al-Salafiyyah al-Wahhābiyyah - Wibowo, Waskito; Fadillah, Nur Aisyah; Madi, Ahmed A. A.; Mabrook, Bassam Hadi Mohammed (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2024)
This article seeks to analyze and focus on institutional Salafism, also referred to as Wahhabism. The term